2021
DOI: 10.1108/ils-08-2020-0206
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing an information environment for supporting learning

Abstract: Purpose This study aims to offer insights into the presence and nature of an information environment provided for young children to support their learning and explore how an information environment for young children can be characterized. Design/methodology/approach Observations of video-recorded public library storytimes were used to investigate the presence and nature of an information environment for young children’s learning. Findings The observations revealed that storytimes provide a rich, multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Overall, it is important that informal learning environments offer these CT opportunities alongside schools, as informal learning environments focus on interest-driven, open-ended experiences that allow children to follow their own interests and direct their own learning process (Falk and Dierking, 2002). In addition, since caregivers often accompany their young children to libraries and museums (Campana, 2021; Wolf and Wood, 2012), the use of accessible materials and approachable CT activities can help families understand how they can incorporate CT into their home environments. Finally, these opportunities help to increase access to CT experiences for young children, particularly for those ages 0–5 years, given that a large percentage of them are not in a formal school environment (Annie E. Casey Foundation, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is important that informal learning environments offer these CT opportunities alongside schools, as informal learning environments focus on interest-driven, open-ended experiences that allow children to follow their own interests and direct their own learning process (Falk and Dierking, 2002). In addition, since caregivers often accompany their young children to libraries and museums (Campana, 2021; Wolf and Wood, 2012), the use of accessible materials and approachable CT activities can help families understand how they can incorporate CT into their home environments. Finally, these opportunities help to increase access to CT experiences for young children, particularly for those ages 0–5 years, given that a large percentage of them are not in a formal school environment (Annie E. Casey Foundation, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging literature and practitioner-focused writings have indicated that public libraries have been focusing on creating library spaces (Hassinger-Das et al, 2020), providing "loose parts" toys (Swadley, 2021), and offering programs (Ruscio, 2019) to better incorporate and facilitate children's unstructured play. For public library storytimes, the use of play has ranged from offering time and space before and after the program for unstructured and less adult-guided play (Diamant-Cohen et al, 2012), to more actively adult-led short, playful elements during the program (Campana, 2021). Understanding more about how educator-led play, and specifically dramatic play, may be effectively sustained and fostered throughout the entirety of the library storytime program holds potential to benefit children's development and move the incorporation of play in storytimes more toward a model of playful learning.…”
Section: Informal Learning Environmentsmentioning
confidence: 99%
“…As one of the most common, and arguably well-known, children's programs in public libraries, storytimes have long been recognized for their role in family engagement and learning for young children and caregivers. Library storytime programs often incorporate a wide variety of elements including songs, rhymes, and chants, books, props, and manipulatives, puppets, music, and movement-based activities to encourage multimodal engagement opportunities (Campana, 2021). Previous research on public library storytimes has found that these programs can support a variety of early learning and school readiness skills including literacy, mathematics, and others for young children (Campana, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations